The Effect of Gargling Areca Nut Extract (Areca catechu L) 2,5% Against Plaque pH and Saliva pH - Prasko Prasko; Yaya Widyatmoko; Sadimin Sadimin (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
ABSTRACTThe most common dental and oral health problems are dental caries and periodontal disease caused by dental plaque. Dental plaque is a soft deposit consisting of microorganisms found on a matrix that is formed and adheres tightly to the tooth surface. Bacteria in plaque will metabolize food waste, especially the type that can be fermented so that it will produce acid. The acid produced will lower the plaque pH to 4.5-5.0 wthin 1-3 minutes and return to normal at pH 7 within 30-60 minutes. Plaque buildup on the tooth surfaces is related to plaque pH salivary pH. The continuous decrease in plaque pH and salivary pH will cause demineralization. The purpose of this study was to determine the effect of gargling betel nut extract (Areca catechu L) 2.5% on plaque pH and salivary pH.The study was a quasi-experiment research with two group pretest-posttest design. The sample used in this study were 16 samples, 6th graders at SDN Pontianak Utara using the Total Sampling method. The sample was instructed to rinse with a 2.5 % betel nut extract moutwash solution and measure the plaque pH and salivary pH before and after gargling. The control group rinsed with 1% povidone iodine (Betadine Moutwash). Data analysis using the tes Wilcoxon to find out the difference between the influence variables and the affected variables.The results of this study based on the test were Wilcoxon test, the results showed that the average plaque pH before and after gargling with betel nut extract was 2.5% 7.06 and 7.22 p-value = 0.000 (p 0.05). The average pH of saliva before and after gargling a 2.5% betel nut extract solution was 6.56 and 5.59 p-value = 0.000 (p 0.05). So it can be concluded that gargling 2.5% betel nut extract solution has an effect on changes plaque pH and salivary pH.